Presenting Norwegian Literature in Czechoslovakia: Norwegian Literature in Czech Translations 1945–1968 - Ficová, Adéla (Scandinavistica Vilnensis, 2023)
Translations contribute to spreading but also shaping of cultural memory. While the choice of titles which get to be translated is contingent on many factors which the publishers take into consideration, decision-making in totalitarian countries is fettered. In communist Czechoslovakia, the final selection of books, and therefore memories, had to meet yet another criterion which deformed the natural literary development – censorship. The article focuses on Norwegian literature which was introduced into Czech between 1945 and 1968. Norwegian literature had already had a strong position on the Czechoslovak literary market since the end of the 19th century and in the first half of the 20th century thanks to several publishing houses, translators, and the introduction of the Nobel Prize in literature. This tradition was first interrupted by the WWII and shortly after again by the communist coup in 1948. Although the restrictions began loosening later, the Soviet intervention in 1968 installed the restrictions again. The object is to present and examine the image of Norwegian literature in Czech literary memory as it was shaped by the cultural policies of totalitarian Czechoslovakia; and to show and explain which type of literature could enter Czech bookshops and libraries. The focus often shifted to a specific literary genre, republishing the earlier works of the Norwegian canon, or works by authors whose work was translated into Czech although they were marginalized in Norway and did not make it into the Norwegian national canon. An important part of such a perception is not only remembering but also forgetting. The article therefore also maps the active suppressing of memories by black-listing particular authors or works. Lastly, the article is also concerned with peritexts of translation, namely introductions and afterwords, as these often contributed to mediation of the transfer.